(untitled) (UNWE Yearbook, 2009)
This research paper makes an econometric study of the interrelationship between economic growth and the development of the banking system in Bulgaria by applying the method of dynamic series analysis. The study verifies the presence of a short-term and long-term causality between the dynamic development of the real and the banking sectors, assesses the presence of a long-term dependency between them, and identifies the specific direction of the impact exerted by such dependency. The study characterizes the role of investments as one of the fundamental transmission mechanisms and maps out forecasts about the type and dynamic development of the interconnection, subject to the study, in a given future period of time. The econometric results indicate that in the conditions existing in Bulgaria, the relation between financial development and economic growth is extremely complicated: in most cases it is two-way, frequently it is contradictory, and manifests clearly expressed specificities under the different monetary regimes. What gains the upper hand, however, are the long-term dependencies and causal effects in the relationships between the two sectors, whereby the dominating direction of the impact during the second period subject to the study is from the real to the financial sector. After the middle of 1997, investments turn out be a significant channel for transmitting effects from the financial system to the real sector of the economy, which is quite non-typical for the preceding period of time. The forecasts for a future period of time indicate the dominating and increasing contribution of economic growth when it is generated by financial development. When we test the hypothesis that financial development is caused by economic growth, however, it is financial variables that have a dominating and declining contribution with time.